Association between Community Ambulation Walking Patterns and Cognitive Function in Patients with Parkinson’s Disease: Further Insights into Motor-Cognitive Links - Aner Weiss; Talia Herman; Nir Giladi; Jeffrey M. Hausdorff (Parkinson's Disease)
Background. Cognitive function is generally evaluated based on testing in the clinic, but this may not always reflect real-life function. We tested whether parameters derived from long-term, continuous monitoring of gait are associated with cognitive function in patients with Parkinson’s disease (PD). Methods. 107 patients with PD (age: 64.9 ± 9.3 yrs; UPDRS motor sum “off”: 40.4 ± 13.2; 25.23% women) wore a 3D accelerometer on their lower back for 3 days. Computerized measures of global cognitive function, executive function, attention, and nonverbal memory were assessed. Three-day acceleration derived measures included cadence, variability, bilateral coordination, and dynamic postural control. Associations between the acceleration derived measures and cognitive function were determined. Results. Linear regression showed associations between vertical gait variability and cadence and between global cognitive score, attention, and executive function (p≤0.048). Dynamic postural control was associated with global cognitive score and attention (p≤0.027). Nonverbal memory was not associated with the acceleration-derived measures. Conclusions. These findings suggest that metrics derived from a 3-day worn body-fixed sensor reflect cognitive function, further supporting the idea that the gait pattern may be altered as cognition declines and that gait provides a window into cognitive function in patients with PD.